Workplace industrial relations in a developing environment: barriers to renewal within unions in Malaysia - Naresh Kumar; Raduan Che Rose; Miguel Martinez Lucio (Wiley, 2013)
In this paper we examine the views of employees from unionized companies and trade union leaders on the barriers to trade union activities in Malaysia through reference to survey data. These barriers are political, social and economic. The system of Malaysian industrial relations is not necessarily anti-union – in theory – but the article points to a range of structural barriers and challenges facing unions. However, the evidence presented also shows that there are major gaps and barriers within trade unions in terms of strategic renewal and organizational change. There are also major issues of union visibility within the workplace and the community. These are partly explained by the lack of systematic support offered by the legal system and employer; yet, there is a real perception gap as far as workers are concerned. Notably, the trade unions have little influence in decision-making processes across a range of human resource management practices and workplace issues. In addition, there are indications that trade unions have not really thought about or developed direct and more imaginative forms of communication in relation to the changing nature of the workforce and the economic context. As a result, internal barriers to change have been shaped by external ones, and this must be considered in any debate on Malaysian industrial relations.